Toward New Paradigms in the Follow Up of Adult Patients With Celiac Disease on a Gluten-Free Diet - Pinto-Sanchez, Maria I.; Bai, Julio C. (Frontiers in Nutrition, 2019)
Gluten free diet is the only available treatment for celiac disease (CeD). Patients with CeD who do not adhere to a strict gluten-free diet (GFD) have been found to have complications involving nutritional deficiencies, increased risk of bone fractures, increased risk of mortality, and certain types of cancers. Complete removal of gluten from the diet in a patient with CeD often results in symptomatic, serologic, and histologic remission. However, strict compliance with the diet is challenging. Long-term follow-up care is needed to assure treatment compliance and positive health outcomes. Monitoring celiac specific serology, nutrient deficiencies, bone mineral density, and assessment of GFD compliance have been recommended in clinical practice. However, there is no consensus on which specific tests and how often they should be performed during the follow up. Here, we have performed a review of the literature on current strategies to follow up patients with CeD. There are new tools for monitoring adherence to the GFD which could change some paradigms in following up treated patients.